A critical review of the environmental impacts of manufactured nano-objects on earthworm species. (1st December 2021) - Adeel, Muhammad; Shakoor, Noman; Shafiq, Muhammad; Pavlicek, Anna; Part, Florian; Zafiu, Christian; Raza, Ali; Ahmad, Muhammad Arslan; Jilani, Ghulam; White, Jason C.; Ehmoser, Eva-Kathrin; Lynch, Iseult; et al.
Abstract: The presence of manufactured nano-objects (MNOs) in various consumer or their (future large-scale) use as nanoagrochemical have increased with the rapid development of nanotechnology and therefore, concerns associated with its possible ecotoxicological effects are also arising. MNOs are releasing along the product life cycle, consequently accumulating in soils and other environmental matrices, and potentially leading to adverse effects on soil biota and their associated processes. Earthworms, of the group of Oligochaetes, are an ecologically significant group of organisms and play an important role in soil remediation, as well as acting as a potential vector for trophic transfer of MNOs through the food chain. This review presents a comprehensive and critical overview of toxic effects of MNOs on earthworms in soil system. We reviewed pathways of MNOs in agriculture soil environment with its expected production, release, and bioaccumulation. Furthermore, we thoroughly examined scientific literature from last ten years and critically evaluated the potential ecotoxicity of 16 different metal oxide or carbon-based MNO types. Various adverse effects on the different earthworm life stages have been reported, including reduction in growth rate, changes in biochemical and molecular markers, reproduction and survival rate. Importantly, this literature review reveals the scarcity of long-term toxicological data needed to actually characterize MNOs risks, as well as an understanding of mechanisms causing toxicity to earthworm species. This review sheds light on this knowledge gap as investigating bio-nano interplay in soil environment improves our major understanding for safer applications of MNOs in the agriculture environment. Graphical abstract: Image 1 Highlights: The first-time review on the ecotoxic effects of manufacture nano objects (MNOs) on earthworms. Studies spanning 2010–2020 reveal that MNOs induce mixed effects on earthworms. Long-term toxicological data needed to actually characterize MNOs risk.